Gestational weight gain adequacy among twin pregnancies in France. Issue 1 (12th October 2022) - Amyx, Melissa; Korb, Diane; Zeitlin, Jennifer; Schmitz, Thomas; Le Ray, Camille
Abstract: The objective of this paper is to describe gestational weight gain (GWG), to assess the applicability of the 2009 Institute of Medicine (IOM) guidelines, and to derive a GWG adequacy classification within a French cohort. We included twins from the national, prospective, population‐based JUmeaux MODe d'Accouchement (JUMODA) cohort study (2014–2015). Following the IOM approach, we selected a 'standard' population of term pregnancies with 'optimal' birthweight (≥2500  g ; n  = 2562). GWG adequacy (insufficient; adequate; excessive) was defined using IOM recommendations (normal body mass index [BMI]: 16.8–24.5 kg [also utilized for underweight BMI]; overweight: 14.1–22.7 kg; obese: 11.4–19.1 kg). Additionally, using the IOM approach, we determined the 25th and 75th percentiles of GWG in our standard population to create a JUMODA‐derived GWG adequacy classification. GWG and GWG adequacy were described, overall and by BMI and parity. In the JUMODA standard population of term twin livebirths with optimal birthweight, mean GWG was 16.1 kg (standard deviation 6.3). Using IOM recommendations, almost half (46.5%) of the women had insufficient and few (10.0%) had excessive GWG, with similar results regardless of BMI or parity. The 25th and 75th percentiles of GWG in the JUMODA standard population (underweight: 13–21 kg; normal weight: 13–20 kg; overweight: 11–19 kg; obese: 7–16 kg) were lower than the IOM recommendations. The IOM recommendations classified a relatively high percentage of French women as having insufficient and a low percentage as having excessive GWG. Additional research to evaluate recommendations in relation to adverse perinatal outcomes is needed to determine whether the IOM recommendations or the JUMODA‐derived classification is more appropriate for French twin gestations. Abstract : Using the 2009 Institute of Medicine (IOM) recommendations to define gestational weight gain (GWG) adequacy in our French cohort classified almost half of women as having insufficient GWG and a relatively low percentage as having excessive GWG. The USA‐derived IOM definition for adequate GWG may not apply in France or in other non‐USA, contemporary obstetric populations. Additional research in large, population‐based contemporary cohorts with prospective GWG ascertainment and assessment of GWG adequacy classifications in relation to adverse outcomes is needed to inform evidence‐based GWG recommendations for twin pregnancies. Key messages: Using the 2009 Institute of Medicine (IOM) recommendations to define gestational weight gain (GWG) adequacy in our French cohort classified almost half of women as having insufficient GWG and a relatively low percentage as having excessive GWG. The USA‐derived IOM definition for adequate GWG may not apply in France or in other non‐USA, contemporary obstetric populations. Additional research in large, population‐based contemporary cohorts with prospective GWG ascertainment and assessment of GWG adequacy classifications in relation to adverse outcomes is needed to inform evidence‐based GWG recommendations for twin pregnancies.